Local and spatial cointegration in the wage curve: A spatial panel analysis for German regions - Reinhold Kosfeld; Christian Dreger (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The wage curve introduced by Blanchflower and Oswald (1990, 1994) postulates a negative correlation between wages and unemployment. Empirical results focus on particular theoretical channels establishing the relationship. Panel models mostly draw on unionized bargaining or the efficiency wage hypothesis. Spatial econometric approaches can be rationalized by monopsonistic competition. However, the approaches either ignore the issue of nonstationarity or treat the data as if it were nonspatial. In this paper, we adopt a global cointegration approach recently proposed by Bienstock and Felsenstein (2010) to account for nonstationarity of regional data. By specifying a spatial error correction model (SpECM), equilibrium adjustments are considered in both space and time. Applying the methodology for West German labour markets, we find strong evidence for the existence of a long-run wage curve with spatial effects.
Keywords: J30; J60; C33; R15; 330; wage curve; regional labour markets; spatial panel models; global cointegration analysis